Asymptotic analysis of propagation of a signal with finite rise time in a dispersive, lossy medium - Ciarkowski, A. (Archives of Mechanics, 1997)
Propagation of an electromagnetic high frequency modulated signal with a finite rise time through a dispersive medium described by the Lorentz model is considered. Asymptotic approximations, based on uniform asymptotic methods, are found for the Sommerfeld and Brillouin precursors, and for the steady state contribution to the propagated field.